Analisis Bibliometrik Perkembangan Financial Statement Fraud Dengan Vosviewer - Nur Mustika (Universitas Pendidikan Ganesha, 2026)
This study aims to determine the development of the number of national and international publications on the topic of financial statement fraud, the study also aims to find out the core journals in international publications, find out how many publication development clusters and also want to know how widespread the distribution of publications on this topic is throughout the world. The method of data collection is by searching data through publications indexed by Scopus on the Publis On Persih application with the keyword financial statement fraud with categories or keywords in the title of the article in the period 2020-2024. The analysis was carried out with Bibliometrics using VOSviewer 1.6.20 software and the results of the study show that the development of the growth of financial statement fraud publications in general has increased, the highest indexed publication data in Scopus occurred in 2024 which reached 75 publications (16.30%), consisting of 14 clusters and most published in the Journal of Business Ethics.